A case of culture‐negative endocarditis causing flail perforated mitral valve - Sriharsha Dadana; Anusha Kondapalli; Vipul Madhwani (Clinical Case Reports, 2024)
Key Clinical Message We describe a case of culture negative endocarditis causing mitral valve perforations and recurrent heart failure admissions.